EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN HIGHER ORDER THINGKING SKILLS (HOTS) SISWA KELAS XI SMA NEGERI 1 BATANG ANAI PADA MATA PELAJARAN GEOGRAFI - Anisa Ul Kamila, Atri; Nofrion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the Problem Based Learning learning model on the Higher Order Thinking Skills (HOTS) abilities of class XI students in Geography subjects at SMA 1 Batang Anai. The background of the study is the results of observations showing that student learning outcomes related to HOTS questions are still low due to the lack of variation in learning models and low student involvement in the learning process. This study uses a quantitative approach with an experimental method and a pretest - posttest control group design. The research sample consists of two classes, namely class XI. F6 as the experimental class and F7 as the control class, with a total of 61 students. Data were collected through pretest and posttest tests, and analyzed using descriptive statistical tests, normality tests, homogeneity tests, t-tests, and N-Gain tests. The results of the study indicate that the application of the PBL model can significantly improve students' HOTS abilities